BEYOND FREUD AND BEHAVIORISM: SUFISM AS THE ROOT OF TRANSPERSONAL PSYCHOLOGY IN UNDERSTANDING HUMAN CONSCIOUSNESS - Anggraini, Leli; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
This article aims to analyze the position of Sufism as an often overlooked intellectual and practical foundation in the birth of Transpersonal Psychology. Through a literature study and comparative analysis approach, this research criticizes the limitations of mainstream psychological paradigms—particularly Freudian Psychoanalysis and Behaviorism—which fail to explain the spiritual dimension and peak experiences of humans. The research findings show that key concepts of Sufism such as fana ' (destruction of the ego ), ma'rifat(divine knowledge), andZikr as a method of developing consciousness, has been discussing the "transpersonal" area centuries before modern psychology formulated it. Sufism is not just a parallel, but functions as a root that provides a comprehensive spiritual journey map. This article concludes that the integration of the Sufi heritage with Transpersonal Psychology can lead to a more holistic understanding of human consciousness, moving beyond pathological models to a model of actualizing the highest human potential. This study recommends further exploration of Sufism practices as a therapeutic modality in the context of contemporary psychology.